Developing a Website for Alif Stone Park of Natuna Regency Using a Desktop-Based QR Code System - Firma Wahdani; Reza Giga Isnanda; Aprilia Kurnianti (Universitas Muhammadiyah Yogyakarta, 2021)
Alif Stone Park is a geosite tourism or rock garden that originated from pre-historic times. It has giant granite stones arranged beautifully along the shores of Sepempang Village, East Bunguran District, Natuna Regency, Riau Islands. Geosite tourism or rock garden is one of the tours that is in great demand by local visitors or visitors from outside who visit Natuna Regency because it has its own historical value and is a target for a photo spot for visitors. But Alif Stone Park has a drawback, namely it does not have a permanent Tour Guide and information that can explain about Alif Stone Park itself. To facilitate the service of providing information on Alif Stone Park, we need a website that is easy to access by visitors. So that when visitors want to know what information is in the Alif Stone Park tourist attractions, visitors have no trouble accessing the website later. The QR code will lead to a website containing Alif Stone Park tourist attractions from their history, origins, location of tourist attractions, information on tourist attractions in Alif Stone Park and others. Therefore, a website was created that uses a qr code scan system. It is hoped that the website or system that has been created can run and help well visitors who will come to visit Alif Stone Park. In making the Alif Stone Park website there are 6 stages that are carried out namely Requirement Gathering, Requirement Analysis, Requirement Specification, Prototyping, Implementation, and Testing. The 6 stages are carried out in stages. In the testing phase, there are 3 tests, namely Developer Testing, Owner Testing, and Visitor Testing. Based on the results obtained from the implementation phase and the testing phase, it can be concluded that the Alif Stone Park website has been successfully created, including the features on the website. The scan system on the website was also successfully created and running well. This website can be accessed using a Qr Code where visitors only need to scan from their respective smartphones.